Student Work Readiness Viewed from Organizational Activity and Entrepreneur Behavior - Diina Auliya; Moh Rifqi Khairul Umam (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
Many fresh graduates are unemployed due to a lack of job readiness. Indonesian Statistics confirm that the number of unemployed diploma and undergraduate graduates continues to grow. This study aimed to determine the effect of organizational activity and entrepreneurial behavior on student work readiness. The population used is students of the Islamic Economics and Business Faculty of UIN Raden Mas Said Surakarta who are still active in college. Data processing applies SPSS version 26. The sampling technique uses convenience sampling to determine the number of samples using the Malhotra formula—data analysis technique using multiple regression analysis. The results showed that organizational activity and entrepreneurial behavior had insignificantly affected readiness in Islamic Faculty of Economics and Business UIN Raden Mas Said Surakarta students.